Investigations on nonlinear optical properties of gold nanoparticles doped fluoroborate glasses for optical limiting applications - Abhiram Jagannathan (2020)
© 2020 Elsevier B.V. Gold nanoparticles (NPs) exhibit strong surface plasmon resonance (SPR) in the visible spectral region. Lithium Zinc Calcium Fluoroborate glasses embedded with Au NPs were synthesized by conventional melt quench technique. The gold NPs embedded glasses exhibited dichroic nature. A small kink around 44.61∘ in the X-ray diffraction (XRD) pattern suggests the presence of Au (2 0 0) in the matrix. High resolution-transmission electron microscopic (HR-TEM) measurements further confirmed the existence of spherical and ellipsoidal Au NPs. Thermogravimetric analysis (TGA) reveals the role of network modifiers in the matrix as the glasses that contained higher concentration of lithium oxide exhibits lower Tg thereby resulting in creation of more non bridging oxides (NBO's). The Z-Scan studies were performed under non-resonant condition (800 nm) to analyze the application of these glasses for optical limiting devices.